2000
DOI: 10.1152/jappl.2000.89.2.629
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-dependent growth hormone release is linked to markers of heightened central adrenergic outflow

Abstract: To test the hypothesis that heightened sympathetic outflow precedes and predicts the magnitude of the growth hormone (GH) response to acute exercise (Ex), we studied 10 men [age 26.1 +/- 1.7 (SE) yr] six times in randomly assigned order (control and 5 Ex intensities). During exercise, subjects exercised for 30 min (0900-0930) on each occasion at a single intensity: 25 and 75% of the difference between lactate threshold (LT) and rest (0.25LT, 0.75LT), at LT, and at 25 and 75% of the difference between LT and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 41 publications
(50 reference statements)
2
26
1
2
Order By: Relevance
“…The effects of leptin modulating satiety are directly related to NO production. A decrease in food consumption induced by leptin infusion was mitigated by L-arginine infusion in chicken 23 . Ventricular intra-brain infusions of leptin promoted an expected suppression of food intake and reduction in nNOS activity; both effects are antagonized by L-arginine infusions 1 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The effects of leptin modulating satiety are directly related to NO production. A decrease in food consumption induced by leptin infusion was mitigated by L-arginine infusion in chicken 23 . Ventricular intra-brain infusions of leptin promoted an expected suppression of food intake and reduction in nNOS activity; both effects are antagonized by L-arginine infusions 1 .…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies showed that L-arginine may act on two fronts in these events, one goes through an amplified signal for the production of GH via stimulus in the anterior hypophysis 25 , and the other through an alternate route in the process of creatine formation and consequently resulting in a sarcoplasmic hypertrophy from increased fluid retention 26 and increased contractile filaments 23 .…”
Section: Recently Prodam Et Almentioning
confidence: 99%
“…Impulses from motor centres directly stimulate both sympathoadrenal and pituitary secretion (Kjaer et al 1987). In addition, markers of central adrenergic outflow precede and are proportionate to increases in hGH after exercise (Weltman et al 2000). Endurance training reduces the plasma catecholamine response to a 30-s sprint (Brooks et al 1985), whilst the plasma catecholamine response to a 30-s sprint increases following sprint training (Nevill et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The actions of GH and testosterone are enhanced by catecholamines, which reflect the acute demands of exercise, and influence force production, muscle contraction rate and energy availability [65][66][67]. Research has reported low-intensity resistance exercise with BFR to increase norepinephrine secretion, in concert with GH and lactate levels, more than without BFR [8,18].…”
Section: Hormonal Responsesmentioning
confidence: 99%